1994
DOI: 10.1016/0550-3213(94)90229-1
|View full text |Cite
|
Sign up to set email alerts
|

Factorized scattering in the presence of reflecting boundaries

Abstract: We formulate a general set of consistency requirements, which are expected to be satisfied by the scattering matrices in the presence of reflecting boundaries. In particular we derive an equivalent to the boostrap equation involving the W-matrix, which encodes the reflection of a particle off a wall.This set of equations is sufficient to derive explicit formulas for W , which we illustrate in the case of some particular affine Toda field theories.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(153 citation statements)
references
References 22 publications
(23 reference statements)
4
149
0
Order By: Relevance
“…Further studies regarding the boundary ATFT at both classical and quantum level may be also found in various articles (see e.g. [13]- [18]). …”
Section: Introductionmentioning
confidence: 99%
“…Further studies regarding the boundary ATFT at both classical and quantum level may be also found in various articles (see e.g. [13]- [18]). …”
Section: Introductionmentioning
confidence: 99%
“…The same spectrum can be obtained using the completely different approach of the bootstrap method. It is based on the pioneering work of Cherednik [21], Ghoshal and Zamolodchickov [9], and Fring and Köberle [22]. This way we shall be able to compare and compliment the results to acquire an even more accurate spectrum.…”
Section: The Bootstrap Methodsmentioning
confidence: 99%
“…They can be derived most easily simply by exploiting the associativity of the so-called Zamolodchikov-Faddeev (ZF) algebra [21] and its extended version which includes an additional generator representing a boundary [22,23,24] or a defect [25,26]. Indicating particle types by Latin and degrees of freedom of the impurity by Greek letters, the "braiding" (exchange) relations of annihilation operators Z i (θ) of a particle of type i moving with rapidity θ and defect operators Z α in the state α can be written as…”
Section: Defect Yang-baxter Equationsmentioning
confidence: 99%